The Use of Modern Digital Technologies in the Design and Technology VET in Ukraine - Kolosnichenko, Maryna; Yezhova, Olga; Pashkevich , Kalina; Kolosnichenko , Olena; Ostapenko, Nataliia (Journal of Technical Education and Training, 2021)
The objective of this paper is to substantiate the system of vocational education and training (VET) of fashion designers and technologists to perform computer modeling and design of the clothes. The use of the developed system of training specialists in fashion design, which provides for the use of CAD systems, contributes to the formation of readiness of future fashion designers to use specialized software in their professional activities. To increase the efficiency of VET, we used the following types of educational projects: development of creative collage, development of artistic sketches of clothes, design of templates for different sizes, use of programs for the 3D design of the clothes. A feature of this study is the selection of the software used in the design of the clothes, namely GraziaCAD and JULIVI CAD. The effectiveness of these types of tasks is confirmed by an experiment, in which 80 students from Kyiv National University of Technologies and Design took part (CG 44 students, EG 36 students). Comparing the results of incoming and outgoing control of the level of students’ readiness, a decrease in the number of students with a low level of readiness for the use of ICT in the professional activities was noted: from 22.7 % to 11.4 % in CG and from 22.2 % to 5.6 % in EG. At the same time, the percentage of students with a high level of readiness increased in both groups: from 29.5 % to 38.6 % in CG and from 25.0 % to 66.7 % in EG. Also, it should be noted that the biggest changes in the number of students with a high level of knowledge took place in EG. According to Pearson’s criterion, the compliance of CG and EG with the level of significance 0.05 was determined, and after the experiment, the difference between CG and EG with 95 % reliability was stated. The results of the study confirm the effectiveness of the generally accepted international practice of using digital design in VET in the field of fashion design and technologies.